Host-Directed Therapies: Modulating Inflammation to Treat Tuberculosis - Krug, Stefanie; Parveen, Sadiya; Bishai, William R. (Frontiers in Immunology, 2021)
Following infection with Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), most human hosts are able to contain the infection and avoid progression to active TB disease through expression of a balanced, homeostatic immune response. Proinflammatory mechanisms aiming to kill, slow and sequester the pathogen are key to a successful host response. However, an excessive or inappropriate pro-inflammatory response may lead to granuloma enlargement and tissue damage, which may prolong the TB treatment duration and permanently diminish the lung function of TB survivors. The host also expresses certain anti-inflammatory mediators which may play either beneficial or detrimental roles depending on the timing of their deployment. The balance between the timing and expression levels of pro- and anti-inflammatory responses plays an important role in the fate of infection. Interestingly, M. tuberculosis appears to manipulate both sides of the human immune response to remodel the host environment for its own benefit. Consequently, therapies which modulate either end of this spectrum of immune responses at the appropriate time may have the potential to improve the treatment of TB or to reduce the formation of permanent lung damage after microbiological cure. Here, we highlight host-directed TB therapies targeting pro- or anti-inflammatory processes that have been evaluated in pre-clinical models. The repurposing of already available drugs known to modulate these responses may improve the future of TB therapy.